Gambaran Status Gizi dan Faktor Risiko Kehamilan di Wilayah Kerja Puskesmas Banyudono II - Hana Mamnukha; Dila Fatiha Sholiha; Dewiyanti Fitria; Agita Dianingsih; Budiyanti Wiboworini (Yayasan Literasi Sains Indonesia, 2025)
Background: Banyudono II Public Health Center has collected data on the condition of pregnant women, but proper data processing has not yet been carried out due to limited resources. Purpose: As part of a community service initiative, graduate students from the Master of Nutrition Science Program at Universitas Sebelas Maret (UNS) assisted in processing and analyzing secondary data from the Nutrition and Family Health Information System (SIGIZI KESGA), developed by the Indonesian Ministry of Health. The activity covered six villages: Cangkringan, Dukuh, Jembungan, Jipangan, Sambon, and Kuwiran. Method: This activity used a descriptive quantitative approach through secondary data analysis. Results and Discussion: Analysis revealed that 27% of pregnant women experienced Chronic Energy Deficiency (MUAC < 23.5 cm), 64% were overweight or obese (BMI ≥ 25 kg/m²), and 27% had high blood pressure (≥140/90 mmHg). Additionally, 10% of respondents were over 35 years old, a high-risk pregnancy group. These findings indicate a double burden of malnutrition—both undernutrition and overnutrition among pregnant women, which increases the risk of complications. Conclusion: The use of available data proved valuable in identifying high-risk pregnant women and designing promotive and preventive interventions. Strengthening data utilization helps enhance maternal health services, particularly in resource-limited settings, and supports the Puskesmas in delivering more comprehensive care.